An enhanced security-aware dynamic packet scheduling scheme for wireless networks using intelligent time slice-based krill herd algorithm. Issue 16 (2nd November 2018) - Singh, Surendra; Tripathi, Sachin; Kumar, Nitin
ABSTRACT: Wireless networks perform computing on grouped users together through networks that suffer with improper scheduling and less security awareness results in terms of bandwidth, increase in error rate, power constraints, authentication problem, etc. In order to tackle these problems, an enhanced security-aware dynamic packet scheduling is implemented by utilizing integrated speed packet scheduling which utilizes node distribution by the krill herd algorithm and packet evaluation by intelligent time slice, and reducing the dimensionality of packets with some evolutionary techniques for transmission. To protect these packets from attacks during transmission, the packets are secured by identifying the malicious node and protecting them with proper authentication by PKI (public key infrastructure) with the handshake of secure exchange of distributed signatures. The experimental execution in NS-3 simulator outcomes shows that the proposed system is more efficient in the packet delivery ratio and security than other existing techniques.